PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDAN PENISTAAN SUKU, AGAMA, RAS, DAN ANTARGOLONGAN MELALUI MEDIA ELEKTRONIK ATAU JEJARING SOSIAL - Wicky Leonardy; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
With the advancement of technology owned by mankind today, mankind has entered a new civilization in which the technology without limits that enable people to carry out its activities. Especially in the field of communication, if the first humans to communicate only with a letter that will get to your destination with a long period of time, is now in the presence of the electronic media and the Internet to make humans more easily communicate and interact remotely with a very fast time. Advance technology also makes legally obligated to evolve with the times, because the new regulations will be needed to address these kinds of new criminal offenses, especially in the field of communications technology.One of the communication media is a social networking community. Social networking is a medium to share information and internet-based communications and electronic media as intermediary. With the social networks also create new criminal offenses can emerge and become a real threat to the wider community. For example, social networking has recently enlivened with their social networking accounts rogue users are posting defamation by elements of racial intolerance against a particular group. Pemostingan reason was quite simple, namely freedom of expression, especially the medium is a personal account on the social network. Posts that eventually provoke anger from the group humiliated, and debasing the pemostingnya back in class. In the end, the situation is even more widespread and affected the real world. For example, the war between the groups for exampleFrom the results of the study conclude that based on the description of the effectiveness of setting the two chapters that ensnare perpetrators of defamation of ethnicity, religion, race, and intergroup through electronic media and social networks should use article more effective, namely Article 28 of Law Number 11 Year 2008 on Information and Electronic Transactions. Because based on factors which reinforce the application of Article 28 is Article 63 paragraph (2) of the Penal Code which is also known in the science of law as a principle of lex specialis derogat legi generalis, namely the rule of law is more specifically override the rule of law more generally. Besides the required extension of enforcement regulations of law to the activities in the virtual world or cyberspace that can accommodate newly emerging criminal offense.Keywords: Law Enforcement, Crime, Actors, Sacrilege, Electronic Media